Minat Siswi Dalam Mengikuti Ekstrakurikuler Futsal Di Sma Negeri 1 Banyuasin 1 - Ahmad R Putra; Rohandi N Satardi; Nursidiq Arizal; Ahmad Hidayat; Kiky Subiyanto (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Physical and sports education is part of the curriculum given to elementary school (SD) to senior high school (SMA) level. With the Penjasorkes in schools, especially high schools, female students can channel their movement abilities. Of the many Physical Education subject matter, there is one material, namely Futsal. Futsal is material that can be obtained from formal and non-formal education. In the process of teaching and learning futsal, the teacher has an important role to increase the interest of his students. To find out the interests of students, must have direct information about the state of interest of these students. What is done is to assess limited external cues such as facial and gesture experiments. Based on this, the purpose of this study was to find out